Relationship On Education Level and Environmental Attitude With Tourist Behavior in Kebun Teh Kabawetan - Herlina Fridayati (Green Publisher Indonesia, 2021)
The purpose of this study was to determine the relationship between the level of education and the attitude of concern for the environment with the behavior of tourists in maintaining environmental cleanliness in the area of ​​the Kabawetan Tea Plantation tourism object, Kepahiang Regency, Bengkulu Province. Research that has been carried out using a quantitative approach, with descriptive methods. Based on data on average annual visits, the total population visited was 138 people. The sample of this research is random visitors who meet researchers who are willing to fill out a complete questionnaire. Behavior that can be observed as many as 53 people. Based on the results of the study, it shows that the relationship between knowledge about environmental protection and the behavior of maintaining environmental hygiene is very close, with a product torque correlation value of 0.787. This proves that the proposed hypothesis is accepted. Therefore, the authors draw the following conclusions: 1) There is a positive relationship between the level of education in maintaining environmental hygiene and behavior; 2) There is a positive relationship between environmental care and environmental protection behavior. environmental Hygiene; There is a positive correlation between attentiveness and hygiene behavior.